A functional role for the ‘fibroblast-like cells’ in gastrointestinal smooth muscles - Kurahashi, Masaaki (Blackwell Science Inc, 2011)
Morphologists have described ‘fibroblast-like cells’ (FLCs) in smooth muscles. In the gastrointestinal tract, FLCs are distributed along processes of enteric motor neurons and between the circular and longitudinal muscle layers. They are close to nerve varicosities and make gap junctions with smooth muscle cells. They are labelled with antibodies for platelet derived growth factor receptor α (PDGFRα) and small conductance Ca(2+)-activated K(+) (SK3) channels. We used transgenic mice with constitutive expression of enhanced green fluorescent protein (eGFP) in PDGFRα(+) cells to isolate and study the function of PDGFRα(+) cells as possible mediators of purinergic neurotransmission. PDGFRα(+) cells expressed purine receptors (P2Y1) and SK3 channels abundantly. Under whole cell voltage clamp some PDGFRα(+) cells generated large amplitude spontaneous transient outward currents that were blocked by apamin (300 nm). Dialysis of cells with Ca(2+) (500 nm) activated large amplitude K(+) currents that were also blocked by apamin. Application of adenosine triphosphate (ATP), adenine diphosphate (ADP) or β-nicotinamide adenine dinucleotide (β-NAD) (1–1000 μm) activated large amplitude, apamin-sensitive K(+) currents in PDGFRα(+) cells that were blocked by the P2Y1 antagonist MRS2500 (1 μm). Responses to purines were not elicited in smooth muscle cells under equivalent conditions, and only very small outward currents were elicited under optimized conditions (e.g. permeabilized patches and high concentrations of ATP; 1 mm). These data show that PDGFRα(+) cells are a novel class of excitable cells with large current densities attributable to SK channels and the molecular and ionic apparatus to mediate enteric inhibitory responses to purines in GI muscles.